2020
DOI: 10.1186/s12939-020-01277-2
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of psychosocial factors to socioeconomic inequalities in mortality among older Australian men: a population-based cohort study

Abstract: Background Among older people, the extent to which psychosocial factors explain socioeconomic inequalities in mortality is debated. We aimed to investigate the potential mediating effect of psychosocial factors on socioeconomic inequalities in mortality. Methods We used data from a prospective population-based cohort (the Concord Health and Ageing in Men Project; baseline recruitment in 2005–2007), in Sydney, Australia. The main outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Cancer survival is known to vary by socio-economic advantage/disadvantage [6][7][8][9][10][11] with this difference partly explained by variations in stage at diagnosis and treatment differences [6]. Recent evidence suggests that psychosocial factors including living alone, being unmarried and higher levels of depression can also negatively impact survival [12,13]. Identifying whether socio-economic and demographic disparities also influence QoL outcomes for cancer survivors and the potential drivers of any differences can inform the type of survivorship care that should be directed to different cancer survivors to help ensure equitable outcomes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer survival is known to vary by socio-economic advantage/disadvantage [6][7][8][9][10][11] with this difference partly explained by variations in stage at diagnosis and treatment differences [6]. Recent evidence suggests that psychosocial factors including living alone, being unmarried and higher levels of depression can also negatively impact survival [12,13]. Identifying whether socio-economic and demographic disparities also influence QoL outcomes for cancer survivors and the potential drivers of any differences can inform the type of survivorship care that should be directed to different cancer survivors to help ensure equitable outcomes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Three studies included only adults younger than 75 years old 24 , 25 , 26 ; one study only included only adults older than 75 years old 21 ; and the remainder included both. 10 , 11 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 Three studies reported the association between living alone and mortality separately for adults younger than 75 years and older than 75 years. 28 , 31 , 33 One study reported the association between living alone and mortality separately for the adults younger and older than 65 years.…”
Section: Resultsmentioning
confidence: 99%
“… 28 , 31 , 33 One study reported the association between living alone and mortality separately for the adults younger and older than 65 years. 11 Two studies included only men 30 , 32 and one only women 27 ; among the mixed-sex cohorts, eight reported the association between living alone and mortality separately for males and females. 24 , 25 , 30 , 31 , 33 , 34 , 35 Most studies reported their outcomes with HR 11 , 24 , 25 , 27 , 28 , 29 , 30 , 32 , 33 , 36 , 37 ; four with RR 23 , 30 , 31 , 34 and four with OR.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Stringhini et al 14 reported that low social integration (eg, family relations, positive/negative support, and loneliness) accounted for a partial degree of cumulative socioeconomic disparities in CVD mortality among British men older than 50 years. Khalatbari-Soltani et al 15 revealed that being unmarried and living alone were both associated with a higher risk of CVD mortality among lower-income men older than 70 years in Australia.…”
Section: Discussionmentioning
confidence: 99%